How organizational Politics Impact workers job related outcomes? - Muhammad Anwar Rashid; Talat Islam; Zeshan Ahmer (Journal of Political Studies, 2019)
The construct perceived organizational politics has become an inspiring catch-all in the eyes of researchers for a decade as it has many negative consequences for employees as well as for the organizations. Most of the past studies have focused on organizational related consequences of organizational politics; however, little has been examined regarding employee related outcomes. Therefore, this study aims at investigating the impact of organizational politics on work engagement, citizenship behaviors and turnover intention. The data from 226 employees working in the banking sector on the basis of convenience sampling was collected and SPSS was used to analyze the data. The results revealed a negative impact on organizational politics on work engagement and citizenship behavior and positive impact on turnover intention. Further, work engagement was noted to partially mediate organizational politics-citizenship behavior, and organizational politics-turnover intention associations. The study contributed to job-demand resource theory and has implications for the policymakers and HR managers.